3(x+4)+x=2(x+4)+7

Simple and best practice solution for 3(x+4)+x=2(x+4)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)+x=2(x+4)+7 equation:


Simplifying
3(x + 4) + x = 2(x + 4) + 7

Reorder the terms:
3(4 + x) + x = 2(x + 4) + 7
(4 * 3 + x * 3) + x = 2(x + 4) + 7
(12 + 3x) + x = 2(x + 4) + 7

Combine like terms: 3x + x = 4x
12 + 4x = 2(x + 4) + 7

Reorder the terms:
12 + 4x = 2(4 + x) + 7
12 + 4x = (4 * 2 + x * 2) + 7
12 + 4x = (8 + 2x) + 7

Reorder the terms:
12 + 4x = 8 + 7 + 2x

Combine like terms: 8 + 7 = 15
12 + 4x = 15 + 2x

Solving
12 + 4x = 15 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + 4x + -2x = 15 + 2x + -2x

Combine like terms: 4x + -2x = 2x
12 + 2x = 15 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + 2x = 15 + 0
12 + 2x = 15

Add '-12' to each side of the equation.
12 + -12 + 2x = 15 + -12

Combine like terms: 12 + -12 = 0
0 + 2x = 15 + -12
2x = 15 + -12

Combine like terms: 15 + -12 = 3
2x = 3

Divide each side by '2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 5p+2=4p+10 | | -y(2xy-yz^2-z^3+2z^2)= | | x+33=2x-12 | | 0.2x-3.4=0.5(x-5) | | [-1-3b]=26 | | -3y=7 | | 14-(x+6)=4x-2 | | 150b+2=195b-1 | | 4x+6=-7+2x+21 | | 49+(-17)= | | 3*(k+10)-(11-4k)= | | 2+[x/6]=3 | | x^4+100=20x^2 | | 12+3b=2 | | 6(2)-4= | | x+x+3+x+3+5=38 | | a+(-17)=32 | | 14+8x+x^2=0 | | [n/8]-5=-4 | | -18x^2+122=0 | | -18x+122=0 | | 4w^2=-2ow-25 | | [x-8]=14 | | -6(6-20n)=20(2n-3) | | [k]=9 | | -3x^2+5x=0 | | a=b-cd | | 71-(5x+6)=5(x+2)+x | | 4(3-2n)-n=-11(n-1) | | 4(x-6)+6=2(x-7) | | x+2=3x+2 | | 5(2-1)=4(2+4) |

Equations solver categories